Apicectomy and simultaneous obturation of root canals: a clinical case report - Castro, Hebert Samapaio de; Cabral, Renata Nunes; Kehrwald, Ricardo; Salmeron, Samira; Casaroto, Ana Regina; Queiroz, Polyane Mazucatto [UNESP] (My University, 2022)
Aim: This case report presents a maxillary lateral incisor that had already being treated by endodontic therapy and apicectomy surgery, but still had a persistent lesion. To maintain the tooth in the oral cavity, a third intervention was necessary in which parendodontic surgery followed by retro-obturation was performed. The aim of this report is to demonstrate the effectiveness of the treatment by means of clinical and radiographic follow-ups (6 and 12 months). Summary: Considering the patient's complaint and the clinical and radiographic aspects, it was decided to perform the parendodontic surgery. The surgery procedures were osteotomy, curettage, apicectomy, root canal retreatment and retrofilling with Mineral Trioxide Aggregate, graft with lyophilized bone and, finally, use of collagen membrane. Through clinical and radiographic examinations were possible to observe that there was good healing of the soft and hard tissues, suggesting total regression of the lesion, and absence of signs and symptoms. Even if periapical lesions persist for a long time after interventions, the association of multiple procedures should be considered to enable the maintenance of the tooth in the oral cavity.
Keywords: endodontic retreatment; Endodontics; mineral trioxide aggregate; parendodontic surgery